2007
DOI: 10.1021/ie070684k
|View full text |Cite
|
Sign up to set email alerts
|

Controlling the Water Content of Biomass Fast Pyrolysis Oil

Abstract: Several methods to control the water content of pyrolysis oil from fast pyrolysis of biomass were evaluated experimentally. Parameters varied were the operating temperature of the condenser, the gas load of the condenser, and the moisture content of the feedstock. Experiments were performed in a continuous bench scale plant (1 kg/h intake) equipped with a fluidized bed reactor. Pine wood with moisture contents between 0 wt % and 20 wt % (as-received basis) was used as feedstock. The mass balance closure was be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
165
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 143 publications
(189 citation statements)
references
References 24 publications
4
165
1
Order By: Relevance
“…Burhenne et al (2013) found that higher feedstock moisture content led to slightly lower char and gas yields upon pyrolysis with minimal changes to the elemental composition of the char. However, this is in disagreement with Westerhof et al (2007) who observed slightly higher char yields with increasing moisture content. The water weight fraction distribution of the feedstocks in the two studies were quite different, 2.4-55.4% in Beyond impacts to the yields, He et al (2009) studied the change in selectivity to the organic fraction produced upon pyrolysis of switchgrass with 5, 10, and 15% feedstock moisture contents.…”
Section: Model 3: Interactions and Linkages Between Primary Componentscontrasting
confidence: 56%
See 1 more Smart Citation
“…Burhenne et al (2013) found that higher feedstock moisture content led to slightly lower char and gas yields upon pyrolysis with minimal changes to the elemental composition of the char. However, this is in disagreement with Westerhof et al (2007) who observed slightly higher char yields with increasing moisture content. The water weight fraction distribution of the feedstocks in the two studies were quite different, 2.4-55.4% in Beyond impacts to the yields, He et al (2009) studied the change in selectivity to the organic fraction produced upon pyrolysis of switchgrass with 5, 10, and 15% feedstock moisture contents.…”
Section: Model 3: Interactions and Linkages Between Primary Componentscontrasting
confidence: 56%
“…Several investigations (Westerhof et al, 2007;He et al, 2009;Burhenne et al, 2013) suggest that feedstock moisture content can also play a role in the yield and product distribution of the organic fraction of the bio-oil. As previously discussed, the presence of water in bio-oil prohibits its direct use and creates challenges to catalytic valorization.…”
Section: Model 3: Interactions and Linkages Between Primary Componentsmentioning
confidence: 99%
“…11a have given the exact fraction of water in the product oil, but a study by Westerhof [50] reported that typically water content in the pyrolysis bio-oil is in the range of 15-35 wt% water content. The low water content in the product predicted here is mainly due to the low moisture content in the feedstock.…”
Section: Product Yield and Compositionmentioning
confidence: 99%
“…However, it should be pointed out that these calculated values from experiments with a specific moist feedstock do not necessarily reflect the behavior and yields of this specific feedstock if it was completely dried by physical means prior to the experiment. It is known that moisture affects the yield distribution of pyrolysis 23 and this should be kept in mind when evaluating and comparing 'dry' balances.…”
Section: Discussionmentioning
confidence: 99%